Քրիստոսաբանական վեճերին առնչվող երեք թարգմանական բնագիր - Մուրադյան, Գոհար («Նաիրի» հրատ.)
Данная публикация содержит: Teкст A. “Четырнадцать глав” папы Льва I (сохранился в рукописи 1305 г. – M500, и в более поздних; примерно в то же время его цитирует Степанос Орбелян в догматическом сочинении); Teкст B. “Письмо Льва к Флавиану”; Текст С. “Энотикон” императора Зенона. Teкст A состоит из выдержек из очень дословного (“грекофильского”) перевода “Возражения к определениям собора в Халкидоне” Тимофея Элура (греческий оригинал утерян). В “Возражениях” эти высказывания папы Льва – в свою очередь выдержки из его “Письма к Флавиану” или “Томоса”. В армянской традиции “Томос” – заглавие “Четырнадцати глав”. Собственно “Томос” Льва, т.e. его “Письмо к Флавиану”, также существует в армянском переводе (Teкст B). Рукопись M2038 (1674 г.) содержит другой, независимый от первого, перевод Письма. Тексты А и В публикуются впервые. “Энотикон” Зенона был известен из “Книги писем” (Գզջտ դխդճռ) и, частично, “Печати веры” (Կձզտ ի՜ս՜պճհ). Мы обнаружили его в рукописях и как самостоятельную единицу. Все три текста сравниваются с параллельными греческими оригиналами. This publication includes the Armenian versions of: Text A. the “Fourteen Chapters” (“blasphemies”) оf Pope Leo I (it exists already in Ms M500 copied in 1305 and later Mss; it was also cited by that time in a dogmatic writing by Stepʻanos Orbelean); Text B. Leo‟s Letter to Flavian; Text C. Emperor Zeno‟s Henoticon. Text A consists of excerpts from the extremely literal (“Hellenizing”) translation of the Refutation of the Decisions of the Council of Chalcedon by Timothy Aelurus (the Greek original is lost). In the Refutation Leo‟s statements are in their turn excerpts from his Letter to Flavian or the Tome. In Armenian tradition, Tome is the title of the “Fourteen chapters” (Text A). Leo‟s Tome proper, i.e. his letter to Flavian, too exists in an Armenian translation (Text B). Ms M2038 (copied in 1674) contains an independent translation of the same letter. Texts A and B have never been published. Zeno‟s Henoticon (Text C) was known only from the Book of Letters (Գզջտ դխդճռ), and partly from the Seal of Faith (Կձզտ ի՜ս՜պճհ). We have found it as an independent text in several manuscripts. All three texts are compared with their parallel Greek originals.
Keywords: Հրապարակումներ; Քրիստոնեություն